Investigation of residual stress, stress relaxation and work hardening effects induced by shot peening on the fatigue life of AA 6005-T6 aluminum alloy - Fernandes, Martin Ferreira [UNESP]; Torres, Marcelo Augusto Santos [UNESP]; Fonseca, Maria Da Penha Cindra; Baptista, Carlos Antonio Reis Pereira (IOP Publishing, 2019)
Fatigue strength improvement of mechanical components is one of the most challenging problems in engineering. One of the known ways to improve fatigue life is by using the shot peening process. However, it is complex to define the optimum shot peening parameters to different materials due to the interaction of several variables. This work aimed to investigate the effect of the complex interaction of surface roughness, the residual stresses induced, the stability of the compressive residual stresses during fatigue cycles, and the work hardening of the surface layers induced by the shot peening process on the fatigue behavior of AA 6005-T6 aluminum alloy at room temperature. Rotating bending fatigue tests (R = -1) were carried out on specimens in the as-machined, as-ground, and shot peened with two different intensities (0.006 N and 0.007 A) conditions. The results indicate that both shot peening conditions were capable of improving fatigue life compared to as-machined condition. However, the best fatigue behavior was achieved for the more severe condition (0.007 A), which was capable of shifting the crack source to beneath the surface, as observed through scanning electron microscopy. Although the maximum compressive residual stress was higher for the more severe condition, it was observed a relaxation of the compressive residual stresses after rotating bending fatigue cycles. It was demonstrated that, despite the stress relaxation and the surface damage induced by shot peening, the work hardening generated by the more severe condition nearby the surface was determinant to the efficiency of the process.
Keywords: AA 6005; aluminum alloy; fatigue; residual stress; shot peening